Their name is today: Reclaiming childhood in a hostile world - Sant, Golden (Journal of Interdisciplinary Studies in Education, 2015)
Childhood should hold some of our best memories. Memories where we played, but in today’s world kids’ childhood is being taken away. In Arnold’s book he talks of ways to reclaim childhood and what children need.